Pengaruh Sikap Dan Keyakinan Konsumen Dalam Keputusan Pembelian Tepung Terigu Merek Gunung Bromo Produk PT. Bogasari Flour Mils Surabaya - I Putu Artaya, (Bisnis dan Manajemen, 2008)
This research aim to know, the influence of customer believe n and customer attitude toward customer buying decision during choice raw material of wheat flour for making noodle and bread. Object of this research is noodle manufacture in Surabaya which is PT Bogasari  Flour Mills. In the same way, this research using dependence and independence variables. Dependence variable is   buying decision and independence variabels are customer believe ( x1) and customer attitude  (x2) . Model of analysis aproach is linear multiple regresion  with 30 respondance which is a customer of PT Bogasari Flour Mills Surabaya. Sample using random sampling with samples take without any selection between respondance . Answer alternatif using ordinal approach with likert scale method. Validation test using correction item total and shown that all item are valid because value of corrected  item total  correlation  biger than valu of r tabel. Its mean quetion items can be uses to show something .In the other hand  for reliable test using Alpha Cronbachs trough  cronbach alpha item test  and the  result is reliable because result of all items bigger than 0.7 (standart correlation)  its mean  if items of question will be use continously will give respond  or result consistatly or never change .Furher more, multiple regresion  result shown that customer believe  (X1) and customer attitude  (X2)  has influence to customer buying decision  (Y) with partial hypotesa test and simultaneously has significan result. Between both variable independence , customer believe  (X1)  has dominant influence trough customer buying decision  (Y). Value corelation between idependent and dependent variable with partial and simultanous indicator together has strong value  above 0.7 . Further more, according this research can show that PT Bogasari  Flour Mills  Surabaya  should  increase and growing positive perception of customer  during build attitude image  and believe image trough customer buying decison